Novel co-culture model of T cells and midbrain organoids for investigating neurodegeneration in Parkinson’s disease - Elizaveta Gerasimova; Amke C. Beenen; Daniil Kachkin; Martin Regensburger; Sebastian Zundler; David B. Blumenthal; Gloria Lutzny-Geier; Beate Winner; Iryna Prots (npj Parkinson's Disease)
Abstract Recent studies demonstrate that brain infiltration of peripheral immune cells and their interaction with brain-resident cells contribute to Parkinson’s disease (PD). However, mechanisms of T cell-brain cell communication are not fully elucidated and models allowing investigation of interaction between T cells and brain-resident cells are required. In this study, we developed a three-dimensional (3D) model composed of stem cell-derived human midbrain organoids (hMO) and peripheral blood T cells. We demonstrated that organoids consist of multiple midbrain-specific cell types, allowing to study T cell motility and interactions with midbrain tissue in a spatially organized microenvironment. We optimized co-culture conditions and demonstrated that T cells infiltrate hMO tissue, leading to neural cell loss. Our work establishes a novel 3D cell co-culture model as a promising tool to investigate the effect of the adaptive immune system on the midbrain and can be used in future studies to address these processes in the context of PD.